1995
DOI: 10.1007/bf00796819
|View full text |Cite
|
Sign up to set email alerts
|

Favorable effects of immunosuppressive therapy in children with dilated cardiomyopathy and active myocarditis

Abstract: Among 68 children with severe dilated cardiomyopathy, 43 (aged 10 months to 15 years) presented with active myocarditis, diagnosed by endomyocardial biopsy. They were divided into four treatment groups: I, controls: 9 patients submitted to conventional treatment (digitalis, diuretics, and vasodilators) for 8.1 +/- 0.7 (SD) months; II, prednisone: 12 patients received conventional therapy plus prednisone; III, azathioprine: 16 patients submitted to conventional therapy plus prednisone and azathioprine; IV, cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 29 publications
0
65
0
2
Order By: Relevance
“…Five papers were excluded for the following reasons: duplication (two studies), 9,10) trial did not use biopsy proven diagnosis (one study), 11) and participants with mixed conditions and unable to extract data (two studies). 12,13) Details of the 5 trials included can be found in the Table. Immunosuppressive agents: Five types of immunosuppressive therapy were used in the randomized control studies: prednisone, 8,14) prednisone combined with azathioprine, 7,15,16) prednisone combined with cyclosporine, 7,16) intravenous immune globulin, 13) and immunoadsorption. 12) None showed a beneficial effect on improving mortality and heart transplantation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five papers were excluded for the following reasons: duplication (two studies), 9,10) trial did not use biopsy proven diagnosis (one study), 11) and participants with mixed conditions and unable to extract data (two studies). 12,13) Details of the 5 trials included can be found in the Table. Immunosuppressive agents: Five types of immunosuppressive therapy were used in the randomized control studies: prednisone, 8,14) prednisone combined with azathioprine, 7,15,16) prednisone combined with cyclosporine, 7,16) intravenous immune globulin, 13) and immunoadsorption. 12) None showed a beneficial effect on improving mortality and heart transplantation.…”
Section: Resultsmentioning
confidence: 99%
“…LVEF: LVEF for inflammatory cardiomyopathy was reported in 4 trials. 7,8,15,16) In the short-term (≤ 28 weeks), there was evidence of heterogeneity between the studies (P = 0.14, I 2 = 48.7%). This could not be explained in terms of the clinical characteristics at baseline or methodological quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a few uncontrolled studies showed benefit with several immune suppressive agents, meta analysis of adult studies did not confirm a significant favourable effect of immunosuppression (Garg et al, 1998, Maisch et al, 1998. There were also investigations to evaluate the results of immune suppressive regime in children with acute myocarditis (Chan et al, 1991, Camargo et al, 1995. However, studies in children are inadequate and yet, no randomized controlled trials are present.…”
Section: Immune Therapymentioning
confidence: 99%
“…However, studies in children are inadequate and yet, no randomized controlled trials are present. In a study (Camargo et al, 1995) conducted among 68 children with severe dilated cardiomyopathy, patients were classified into either conventional treatment or given one of three immune suppressive agents, prednisolone, prednisolone plus azathioprine and prednisolone with cyclosporine. Children taking immunosuppression treatment with a second agent, demonstrated enhanced hemodynamic parameters, as well as histological improvement in inflammation.…”
Section: Immune Therapymentioning
confidence: 99%